2019
DOI: 10.1002/met.1776
|View full text |Cite
|
Sign up to set email alerts
|

Frequency analyses of extreme precipitation events in Western Black Sea Basin (Turkey) based on climate change projections

Abstract: The impacts of climate change on extreme precipitation events in the Western Black Sea Basin of Turkey were investigated by using the annual maxima (AM) and peaks over threshold (POT) methods. Daily precipitation data measured between 1971 and 2000 at nine meteorological stations and projected and dynamically downscaled precipitation data from the outputs of GFDL‐ESM2M, HadGEM2‐ES and MPI‐ESM‐MR global circulation models (GCMs) under Representative Concentration Pathway 4.5 (RCP4.5) and RCP8.5 scenarios were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…As a consequence of these events, technical failures and disasters may occur, which in turn often give rise to big losses for society and the economy [9,12,17,20,31,37,38]. Scientific reports show an increased risk caused by extreme meteorological phenomena in recent years in different regions of the world, including intense precipitation [13,15,21,39,42]. Nevertheless, there are still not enough publications on the temporal and spatial variability of EDPr in different climatic zones, particularly in the warm temperate transitional zone to which the present study is dedicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of these events, technical failures and disasters may occur, which in turn often give rise to big losses for society and the economy [9,12,17,20,31,37,38]. Scientific reports show an increased risk caused by extreme meteorological phenomena in recent years in different regions of the world, including intense precipitation [13,15,21,39,42]. Nevertheless, there are still not enough publications on the temporal and spatial variability of EDPr in different climatic zones, particularly in the warm temperate transitional zone to which the present study is dedicated.…”
Section: Discussionmentioning
confidence: 99%
“…In Scandinavia, daily and multi-day intense precipitation are likely to rise by 60% in 2071-2100 according to the RCP4.5 scenario, or even by 100% according to the RCP8.5 scenario [20]. On the other hand, by the end of the present century, in the north of Turkey the frequency of storms will have risen on average by 29% according to the RCP4.5 scenario, and by about 37% according to RCP8.5 [21]. In Central Europe, the biggest increase in intense precipitation by the year 2100 will occur in the winter season.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, increasing nonstationarity can be one of the reasons of the extreme precipitation that the region faces. Balov and Altunkaynak (2018) [56] also reported an increase in the magnitude and frequency of extreme events, however, these results vary spatially for the western Black Sea region. They also found that the method selected for calculation, such as annual maxima or peak over the threshold, can influence the results.…”
Section: Figure 4 Map Of Non-stationary Effect -Hourly Storm Durations -Model 1-2-3 Respectivelymentioning
confidence: 95%
“…For Turkey, for instance, the projections showed that a decrease is expected in southern parts and a slight increase in the northern parts in the total yearly precipitation amount [3]. On the other hand, as a result of global warming the capacity of the atmosphere to hold water has been increased which lead to an increase in the global precipitation [4][5][6][7][8][9]. In this context, a common way to have a knowledge of future extreme precipitation events is to investigate the trend in the longduration time series of historical records [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%